(untitled) (Historia y Grafía, 2022)
Reseña crítica de Giuseppe Marcocci. The Globe on Paper. Writing Histories of the World in Renaissance Europe and the Americas. Trans. Richard Bates. Oxford: Oxford University Press, 2020.